Impact of adverse pregnancy outcomes on brain vascular health and cognition - Wolfova, Katrin; Miller, Eliza C (Research and practice in thrombosis and haemostasis, 2024)
A State of the Art lecture titled "Impact of Adverse Pregnancy Outcomes on Brain Vascular Health and Cognition" was presented at the International Society on Thrombosis and Haemostasis Congress in 2023. Adverse pregnancy outcomes, encompassing conditions such as gestational hypertension, eclampsia, preeclampsia, preterm birth, fetal growth restriction, stillbirth, and gestational diabetes, may form part of an underrecognized pathway from early adulthood reproductive health factors to later-life vascular cognitive impairment and dementia in women. Adverse pregnancy outcomes are caused by dysregulated vascular and metabolic adaptations during pregnancy, and these pathophysiological changes may persist after delivery. Adverse pregnancy outcomes may contribute to the increased risk of cognitive impairment and dementia directly through vascular and metabolic dysregulation and subsequent development of cardiovascular diseases, or other biological processes may be at play, such as shared maternal risk factors. Extensive epidemiologic evidence has shown that many cognitive impairment and dementia cases may be prevented or delayed by strategies targeting midlife cardiovascular health. Despite the recognized importance of adverse pregnancy outcomes for cardiovascular health, the literature on associated long-term health outcomes is limited. In this State of the Art review article, we summarize the current epidemiologic evidence on the relationship between adverse pregnancy outcomes and cognitive impairment and dementia and provide an overview of the potential pathophysiological mechanisms. Finally, we summarize relevant new data on this topic presented during the 2023 International Society on Thrombosis and Haemostasis Congress.
Keywords: preeclampsia; cardiovascular disease; dementia; pregnancy outcome; eclampsia